The interplay between trauma, substance abuse and appetitive aggression and its relation to criminal activity among high-risk males in South Africa. (January 2017) - Sommer, Jessica; Hinsberger, Martina; Elbert, Thomas; Holtzhausen, Leon; Kaminer, Debra; Seedat, Soraya; Madikane, Solomon; Weierstall, Roland
Abstract: Background: In persistently unsafe environments, the cumulative exposure to violence predicts not only the development of posttraumatic stress disorder (PTSD), but also of increased aggression and violent outbursts. Substance use disorders interact with these developments, as drug consumption may blunt symptoms and also reduce the threshold for violent acts. Investigating the interplay between these variables and the possible cumulative effect of drug abuse on the attraction to cruelty is a crucial step in understanding the cycle of violence and developing intervention programs that address this cycle in violence-troubled communities such as low-income urban areas in South Africa. Methods: Young males at risk (N = 290) were recruited through a reintegration center for offenders in Cape Town. We assessed types of traumatic events experienced, PTSD symptom severity, appetitive aggression, committed offenses and patterns of drug abuse prior to the perpetration of violence. Results: Path-analyses confirmed a positive relationship between exposure to traumatic events and PTSD symptom severity, appetitive aggression, the number of committed offenses and drug abuse prior to violence. PTSD symptoms were positively associated with the propensity toward aggression. Furthermore, more severe drug abuse was related to higher attraction to violence and more committed offenses. Conclusions: We conclude that like exposure to violence, drug abuse may play a key role in the attraction to aggression and criminal acts. Measures of violence prevention and psychotherapeutic interventions for trauma-related suffering may not be effective without enduring drug abuse rehabilitation. Highlights: Traumatic experiences positively related to posttraumatic stress and drug abuse Violence exposure affiliated with more aggressive tendencies and cruel behavior Drug abuse prior to violence commission linked to higher attraction to cruelty Substance intake before crime perpetration associated with more committed offenses Reducing substance abuse may lower high violence levels among young South Africans.